2011
DOI: 10.1073/pnas.1017200108
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a bacterial cell surface decaheme electron conduit

Abstract: Some bacterial species are able to utilize extracellular mineral forms of iron and manganese as respiratory electron acceptors. In Shewanella oneidensis this involves decaheme cytochromes that are located on the bacterial cell surface at the termini of transouter-membrane electron transfer conduits. The cell surface cytochromes can potentially play multiple roles in mediating electron transfer directly to insoluble electron sinks, catalyzing electron exchange with flavin electron shuttles or participating in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
375
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 308 publications
(397 citation statements)
references
References 42 publications
16
375
4
Order By: Relevance
“…Therefore, before electron transport can take place, these particles would make contact with the surfaceexposed MtrC that completes the electrical connection through MtrCAB to the cell interior. Structural studies of the MtrC homolog, MtrF, revealed two solvent-exposed hemes situated at opposite ends of a staggered octaheme chain, inferring one of these hemes contacts MtrA to accept electrons from the cell, whereas the other acts as an egress site for transfer of electrons to closely associated mineral material (12). Theoretical studies have estimated potential charge transfer rates through MtrF using the distances between the hemes in the octaheme chain to calculate theoretical electron-hopping rates between redox sites (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, before electron transport can take place, these particles would make contact with the surfaceexposed MtrC that completes the electrical connection through MtrCAB to the cell interior. Structural studies of the MtrC homolog, MtrF, revealed two solvent-exposed hemes situated at opposite ends of a staggered octaheme chain, inferring one of these hemes contacts MtrA to accept electrons from the cell, whereas the other acts as an egress site for transfer of electrons to closely associated mineral material (12). Theoretical studies have estimated potential charge transfer rates through MtrF using the distances between the hemes in the octaheme chain to calculate theoretical electron-hopping rates between redox sites (20).…”
Section: Discussionmentioning
confidence: 99%
“…The spectroscopic and biochemical properties of MtrA and MtrC have been established, and structures of the MtrC family members MtrF and undecaheme A (UndA) have allowed the generation of MtrC homology models (12,13). The exposure of MtrC and the partnering outer-membrane cytochrome A (OmcA) on the cell surface is well documented (14).…”
mentioning
confidence: 99%
“…and Geobacter spp., that can use electron acceptors residing outside the cell for respiration (3). For example, in the case of Shewanella, it is proposed that the CymA-MtrA-MtrC complex comprised of 3 multiheme c-type cytochromes totaling 24 hemes acts as a multistep conduit that conducts respired electrons originating in the cytoplasm from the inner membrane through the periplasm and outer membrane to the cell outer surface (4)(5)(6). Outside the cell, both Shewanella and Geobacter secrete nanometer scale diameter, micrometer scale long proteinaceous filaments, referred to as pili and microbial nanowires (7), that extend from their outer surfaces into the extracellular matrix (ECM) thought to be involved in extracellular electron transport processes, including cell-to-cell electron transfer (8) and reduction of insoluble oxidants (9).…”
mentioning
confidence: 99%
“…By diffusing between the OMMCs and the solid substrate, the flavins can shuttle two electrons from the microbe to the solid (11,18). Flavin reductase activity has been observed for the purified OMMCs (8,19), and mutants deficient in extracellular FMN…”
mentioning
confidence: 99%
“…Recent work (8,9), provided the first structures of OMMCs from Shewanella and revealed that ten hemes were bound as a "staggered cross" on the cell surface (Fig. 1).…”
mentioning
confidence: 99%